Behavioral Transformation Through "Aesthetic Education of Humanity" - Sonika Sonika (Jurnal Maitreyawira, 2020)
Education as a sub-system of the world must adapt, connect, and be compatible with the directions of the strategic environmental tendencies. Education was seen as an interdisciplinary context and a multidimensional development factor with human beings become both goals and instruments. Through education, the existence and the nature of human beings are constantly studied and explored from various disciplinary perspectives. Human beings as creatures and subjects of education that must be improved by quality and behavior through the transformation of moral education, and as a development instrument, that means human beings as developmental behavior that must have high ability, moral ethics, and high character to participate in the nation and state development. The needs of educational reforms that will bring a major impact on life bring us a new atmosphere of change that drives us to build new cultures, new civilizations, new life values, ​​and the new morality, organized a more civilized education of the future, by returning to nature, life balance, harmonization, naturalism, and love. Implementation of the concept: "Aesthetic Education of Humanity" will change the old paradigm to the new paradigm.